2016
DOI: 10.1111/mice.12225
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Networked Control of Building Structures

Abstract: The article presents a new method for the design of decentralized networked switched controllers to mitigate the response of building structures under earthquakes. It consists of two phases. The first phase generates low-order gain matrices based on the linear quadratic Gaussian (LQG) control design. It includes a substructural approach when the equations of motion of substructures are extracted from the equation of motion of the overall structures described by a finite element in-plane (2-D) model. Appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Applications of gravitational search algorithms [4], simulated annealing [5] and central force metaheuristic optimization [6] as nature-inspired conceptual frameworks in engineering are presented. Much attention is being paid to vibration control and the health monitoring of buildings and engineering structures [7][8][9][10][11], including bridges [12,13] and high-rise buildings [14][15][16]. A comprehensive review of tuned mass dampers for the vibration control of structures was provided [17].…”
Section: Introductionmentioning
confidence: 99%
“…Applications of gravitational search algorithms [4], simulated annealing [5] and central force metaheuristic optimization [6] as nature-inspired conceptual frameworks in engineering are presented. Much attention is being paid to vibration control and the health monitoring of buildings and engineering structures [7][8][9][10][11], including bridges [12,13] and high-rise buildings [14][15][16]. A comprehensive review of tuned mass dampers for the vibration control of structures was provided [17].…”
Section: Introductionmentioning
confidence: 99%
“…Giron and Kohiyama () present a decentralized control scheme based on SMC for vibration control of a small‐scale model of a 60‐story high‐rise building with a vibration control device and a shaking table experiment. Based on LQG and neural network control algorithms, Bakule, Reh'ak, and Pap'ık () present a decentralized networked switched control scheme for vibration control of building structures subjected to ground motions.…”
Section: Decentralized Control Algorithmsmentioning
confidence: 99%
“…In the past few decades, structural control, including passive, active, and semi‐active control, has been advanced to ameliorate the effects of extreme dynamic loading . In particular, significant research has been reported in the areas of active and semi‐active control of structures…”
Section: Vibration Control Of Diagridsmentioning
confidence: 99%